Nutritional knowledge levels and food preferences of teachers - Mehmet Emin Parlak; Dilek Ener (Medicine Science, 2023)
Nutritional knowledge includes knowing nutritional processes, major nutritional sources of foods, the relationship of diet to health and disease, and dietary recommendations. This study aimed to determine teachers' basic nutrition and nutrition-health knowledge levels, who are important opinion leaders in society, and to evaluate their food preferences. The research, a cross-sectional study, was carried out in a district in 2022. 280 teachers were included in the research. The survey form consists of 14 questions about sociodemographic information and nutritional preferences; and 32 questions on the "Nutrition Knowledge Level Scale for Adults" (NKLSA). The t-test in independent groups, Pearson Correlation and the Chi-Square test were used for statistical analysis. More than half of the teachers had a medium level of basic nutritional knowledge, nearly half had a good level of food preferences and a 52% correlation between their knowledge levels. The frequency of those with poor basic nutritional knowledge is significantly higher in men than in women. When the teachers' body mass indexes, daily water consumption, breakfast habits, number of daily meals, and skipping meals were evaluated according to information about nutrition, no significant difference was found in basic nutritional knowledge scores and food preference scores. It should be ensured that teachers have access to the right information sources about nutrition, and awareness activities should be carried out for nutrition, including students, to obtain accurate information about nutritional information and food preferences. [Med-Science 2023; 12(1.000): 1-8]